2020
DOI: 10.24974/amae.14.3.401
|View full text |Cite
|
Sign up to set email alerts
|

A Culturally Validated Model of Student Success Services and Academic and Curriculum Enhancements at a Hispanic-Serving Institution

Abstract: Though college enrollment rates for Mexican-American students have increased over the past years, Mexican-Americans still have one of the lowest rates for degree completion. However, more work is recognizing the strengths of students of Mexican descent, particularly those related to culture such as familism, and calling for asset-based programs that validate the student to increase student retention and persistence. Programs infused with such an approach likely address aspects that improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Culturally relevant pedagogy and validation of courses in the PASO program reveal increased first‐year writing‐intensive course pass rates. A recent study across three cohorts of Latinx students enrolled in these courses showed significantly higher pass rates than in non‐validated courses (Romero et al., 2020). In the study, students described culturally relevant aspects of the course.…”
Section: California State University San Marcosmentioning
confidence: 98%
See 4 more Smart Citations
“…Culturally relevant pedagogy and validation of courses in the PASO program reveal increased first‐year writing‐intensive course pass rates. A recent study across three cohorts of Latinx students enrolled in these courses showed significantly higher pass rates than in non‐validated courses (Romero et al., 2020). In the study, students described culturally relevant aspects of the course.…”
Section: California State University San Marcosmentioning
confidence: 98%
“…To better address the needs of this population, the university's faculty, staff, and administrators applied for and received a Title V grant from the U.S. Department of Education to develop a program aimed at first‐year Latinx students named Pathways to Academic Success and Opportunities (PASO). Based on a model of Latino student empowerment and on validation theory that infuses culturally relevant pedagogy and curriculum into the experience (Rendón, 1994), PASO aims to increase retention and graduation rates amongst Latinx students by creating a culturally relevant curriculum and enhancing culturally responsive student support services (Romero et al., 2020). With roots in feminist theories, validation theory argues that when staff and faculty actively engage in an “enabling, confirming, and supportive process” (p. 44) in and out of the classroom, they are fostering the academic and interpersonal development of students from first‐generation and low‐income backgrounds (Rendón, 1994).…”
Section: California State University San Marcosmentioning
confidence: 99%
See 3 more Smart Citations